Measuring Users’ Satisfaction with Tourism Website Contents and their Intention of Future Recommendations - Milojica, Vedran (Turizam, 2019)
Globalization influenced significantly tourism industry in terms of acceleration of changes in the tourist market, with a particular accent on the increase of tourist movements and changes in tourist preferences. One of the reasons with a significant impact was the development of the Internet which resulted in easier obtaining of information about tourist destinations and their offer, especially through use of websites created primarily for the presentation and promotion of tourist offer. Contemporary tourists prefer to travel "virtually", respectively search for details about a destination online before making a decision about visiting it. In order to achieve maximum success in turning potential tourists into visitors, tourist websites need to be created as an ideal combination of images and texts which will reveal the destination´s particularities and stimulate a positive decision in the decision-making process. In order to determine its success, the website needs to be evaluated through determining website user´s attitudes towards its contents. The purpose of this paper is to determine the website user´s level of satisfaction post-browsing the website contents on the example of the official website of the Tourist Board of Zagreb, and whether website users would be willing to recommend it to others in search for information about the destination. The following scientific methods will be used: inductive and deductive method, method of analysis and synthesis, statistical methods (descriptive statistical analysis, correlation and regression analysis), etc. It is expected that the results of the empirical research will determine all the website´s advantages, as well as the potential weaknesses, all of them aimed at its improvement, which will have a positive influence on better presentation of tourist offer, attracting higher number of tourists, which will finally result in achieving competitiveness on the tourist market.
Keywords: Zagreb; websites; Website Contents; Website; Users with Website; tourist market; tourist; success; search; Satisfaction of Users; Satisfaction; offer; Measuring Satisfaction; market; destinations; Destination; changes on the tourist; attracting